(untitled) - Harun, Adrianne (New York, 2001)
that calls to mind such greats as Alice Munro and Andre Dubus. Here are drifters, waitresses, horse trainers, housewives, a Nigerian foreign exchange student, a fisherman's wife, a cat with a cause. Blending magical realism and a pitch-perfect ear for the expressions of the human heart, Adrianne Harun presents a cast of unforgettable characters caught in limbo between their reality and their dreams.
Keywords: United states,Nigerians,Students, foreign; Social life and customs; 20th century; United states,United states